Development and validation of rapid eDNA detection method for yellow mud turtle, Kinosternon flavescens: a field study in South Texas, USA - Rishan, Sakib Tahmid; Kline, Richard J.; Rahman, Md Saydur (Frontiers in Conservation Science, 2025)
The conservation of freshwater turtle species depends on precise and effective monitoring techniques. Environmental DNA (eDNA) analysis is a potential method for identifying cryptic and elusive turtle species in aquatic ecosystems. eDNA analysis can help to identify key regions for conservation efforts and monitor changes in population levels over time. This study aims to evaluate the effectiveness of a rapid eDNA detection method for the yellow mud turtle (Kinosternon flavescens, an indicator species that is endangered in some states in the USA), which inhabits local oxbow lakes (e.g., resacas) in Cameron County, South Texas. A species-specific nested PCR assay was designed to enhance the detection of yellow mud turtle species. Water samples were collected from five locations within Cameron County for the detection of yellow mud turtle eDNA. Our results revealed the presence of yellow mud turtles in two out of the five surveyed locations. Our study shows great potential for eDNA monitoring for yellow mud turtle species. This study also provides insights on using eDNA monitoring to protect yellow mud turtle species and recommendations for future research and conservation initiatives.